A combination of circulating tumor cells and CA199 improves the diagnosis of pancreatic cancer. Issue 5 (25th March 2022) - Chen, Junliang; Wang, Huaitao; Zhou, Lei; Liu, Zhihao; Tan, Xiaodong
Abstract: Background: Early diagnosis of pancreatic ductal adenocarcinoma (PDAC) is difficult due to the lack of effective screening tests. CA199, the standard biomarker for PDAC management, is not sufficiently reliable for early diagnosis. This prospective study aimed to evaluate whether circulating tumor cells (CTCs) could complement or perform better than CA199 in determining PDAC. Methods: A total of 168 blood samples were collected from 80 patients with PDAC, 32 patients with acute pancreatitis, 22 patients with benign pancreatic masses, and 34 healthy donors. CTCs were detected by a novel system combining negative enrichment with immunostaining and fluorescence in situ hybridization (NE‐imFISH). Next, ROC curves and AUC analyses were conducted to assess diagnostic abilities of CA199, CTCs, and the combination of the two biomarkers in PDAC. Results: CTCs were stained as CD45–/DAPI+/CEP8 ≥3. With 2 CTCs/3.2 ml as the cut‐off value, the sensitivity/specificity of the CTC number was 0.76/0.94, which was comparable to that of CA199 (0.78/0.83; Delong test p = 0.3360). Improved performance was achieved through a logistic regression model integrating CA199 and CTC number (AUCCTC+CA199 = 0.95, AUCCA199 = 0.80, AUCCTC number = 0.85; Delong test p vs . CA199 < 0.0001 and p vs . CTC number = 0.0002). CTC subtype was inferior to CTC number as a diagnostic marker (AUCCTC subtype = 0.73; Delong test p vs . CTC number < 0.0001). Conclusion: The dual‐marker panel consisting of CA199 and CTC number can significantly improve upon the diagnostic performance of CA199 alone, highlighting the promising clinical utilization as an effective strategy for PDAC surveillance. Abstract : In this prospective study, the NE‐imFISH strategy was employed to identify CTCs in 80 PDAC patients and 88 controls, which were characterized by CD45–/DAPI+/CEP8 ≥3. As individual biomarkers, CTC number was comparable to CA199 in detecting PDAC. Of note, the dual‐marker panel consisting of CA199 and CTC number can significantly improve upon the diagnostic performance of CA199 alone.